Evaluasi Tax Holiday pada Penyerapan Tenaga Kerja Industri Pionir - Muhammad Ihsan Saifullah; Minerva Muhibbana; Danandjaja Rosewika Toriq Budihardja (Politeknik Ganesha Medan, 2026)
Tax holiday remains one of Indonesia’s main fiscal instruments for attracting investment into pioneer industries. However, in capital-intensive sectors, policy effectiveness cannot be assessed solely from investment realization because forgone tax revenue must also be matched by meaningful employment outcomes, domestic capacity building, and sustainable industrial development. This study aims to evaluate the effectiveness of tax holiday in pioneer industries from the perspective of labor absorption. The analysis also examines how investment incentives relate to employment quality, skills formation, foreign worker dependency, social and environmental externalities, and policy sustainability in the era of global minimum tax. This study uses a qualitative evaluative case study based on secondary data from nineteen journal articles, three ministerial regulations, and relevant institutional publications. The analysis compares a petrochemical project in Cilegon and a nickel-downstreaming industrial zone in Morowali. The results show that tax holiday continues to function as an investment-entry signal, but its labor impact is uneven. In capital-intensive industries, employment creation is concentrated in the construction phase, while strategic technical positions remain constrained by skills mismatch and limited domestic readiness. The Morowali case further indicates that rapid industrial expansion may generate unequal benefit distribution and external costs that reduce net social benefit. Therefore, tax holiday is more effective as an investment-attraction instrument than as a stand-alone employment policy. Its effectiveness will increase if it is redesigned as a conditional incentive linked to local workforce development, technology transfer, and environmental compliance.